2019
DOI: 10.1128/jcm.01866-18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the MicroScan Colistin Well and Gradient Diffusion Strips for Colistin Susceptibility Testing in Enterobacteriaceae

Abstract: Many laboratories are unable to perform colistin susceptibility testing. Diffusion-based antimicrobial susceptibility testing methods are not recommended, and not all laboratories have the capacity to perform broth microdilution (BMD). Using a multistep tiered approach, we investigated whether the adapted use of the MicroScan colistin well (4 g/ml) could enhance laboratory capacity for the detection and subsequent molecular characterization of colistin-resistant Enterobacteriaceae. For the MicroScan colistin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…MicroScan Colistin Well is a newly developed kit for detection of colistin resistance in Gram-negative bacteria [19] The principle of Rapid ResaPolymyxin Acinetobacter/ Pseudomonas NP test is based on the visual detection of the reduction of the resazurin reagent, a viability colorant that is observed by color change (blue to purple or pink). Interestingly, in the current study, no significant color changes were observed in colistin-resistant P. aeruginosa after the addition of the resazurin reagent for 1 h. After prolonging the observation time for another 1 h, the color changed from blue to purple.…”
Section: Discussionmentioning
confidence: 99%
“…MicroScan Colistin Well is a newly developed kit for detection of colistin resistance in Gram-negative bacteria [19] The principle of Rapid ResaPolymyxin Acinetobacter/ Pseudomonas NP test is based on the visual detection of the reduction of the resazurin reagent, a viability colorant that is observed by color change (blue to purple or pink). Interestingly, in the current study, no significant color changes were observed in colistin-resistant P. aeruginosa after the addition of the resazurin reagent for 1 h. After prolonging the observation time for another 1 h, the color changed from blue to purple.…”
Section: Discussionmentioning
confidence: 99%
“…Gradient diffusion is generally regarded as an inaccurate method for colistin susceptibility testing. However, historical data have been highly variable, ranging from excellent agreement for Enterobacterales (16)(17)(18) to either moderate (9,(19)(20)(21) or high (2,8,11,12,22,23) rates of errors, particularly VMEs. This variability is likely attributable to multiple factors, in particular the diversity of isolates evaluated in each study, as represented by MIC distributions, species and strain types, and mechanisms of resistance, including heteroresistance.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of very major errors (VMEs) are a major concern for disk diffusion and gradient agar diffusion tests, and these methods pose a significant risk of failing to detect resistant isolates (11,12). This is particularly disappointing for gradient agar diffusion, as gradient strips are widely available, simple to set up and interpret, and in contrast to disk diffusion, also provide MICs.…”
mentioning
confidence: 99%
“…Antimicrobial susceptibility testing was performed by MicroScan autoScan-4 system using Microscan dehydrated broth microdilution negative MIC Panel Type 44 (NM44) (Beckman Coulter, Inc. USA) following the manufacturer's guidelines [67]. The following antibiotics were tested in the panels: amikacin, aztreonam, cefepime, ceftazidime, cipro oxacin, doripenem, gentamicin, imipenem, levo oxacin, meropenem, piperacillin/tazobactam, piperacillin and tobramycin.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%